Blockchain Technology and Its Impact on Accounting Information Reliability and Quality in Iraqi Banks - Sarhan Ajaj Alo (Studi Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study investigates the impact of applying blockchain technology on enhancing the reliability and quality of accounting information in Iraqi banks, addressing persistent challenges of weak transparency, data manipulation risk, and outdated financial information systems. Methodology: A descriptive-analytical design was used with a structured questionnaire distributed to 140 employees from ten Iraqi banks, including accountants, auditors, managers, and IT staff. Data were analyzed using SPSS with descriptive statistics and linear regression. Results: Blockchain technology has a significant positive effect on accounting information reliability and quality (R = 0.498; R² = 0.413; F = 47.439; p < 0.001). A one-unit increase in adoption improves accounting information quality by 35%, with all dimensions scoring above the neutral midpoint (3.0). Conclusions: The findings confirm that blockchain technology substantially enhances data accuracy, reduces manipulation, strengthens internal controls, and supports real-time financial transparency in Iraqi banking institutions. Limitations: The study is limited to a convenience sample of ten Iraqi banks and relies solely on self-reported perceptions, which may not fully capture technological implementation realities across the broader banking sector. Contribution: This research contributes empirical evidence from an emerging economy context, providing a scientific framework for policymakers and practitioners to guide blockchain adoption in accounting information systems within Iraq and comparable developing nations.